Improvement of ecological taxation with purpose to stimulate the nature protection activity in Ukraine - Костюк, У. З. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
In the article the ecological taxes role as one of the effective instruments of stimulation mechanism of nature protection activity is considered. Existing privileges in taxation of nature protection activity in Ukraine were analyzed. The differences between corresponding items of taxation and ecological legislation were found out. It was proposed the changes for tax legislation.